Computer Forums 1 = 2
 Register FAQ Members List Calendar Search Today's Posts Mark Forums Read

 11-14-2005, 11:42 PM #1 BSOD   Join Date: May 2005 Posts: 2,734 1 = 2 Assume that A = B. AČ = AB AČ - BČ = AB - BČ (A + B)(A - B) = B(A - B) A + B = B B + B = B 2B = B 2 = 1 And there you have it! One is equal to two. Your goal? Find the error in the proof. First to find it gets a big bear hug from a mushroom. __________________
 11-15-2005, 06:18 AM #2 Site Team   Join Date: Mar 2005 Posts: 13,081 Re: 1 = 2 2b=b - - 2 2 B=1 __________________
 11-15-2005, 06:52 AM #3 In Runtime     Join Date: Nov 2005 Posts: 348 Re: 1 = 2 god it 2 late :S i'm saying that 2= Cat X Mushroom all divided by a pony __________________ Yes I have another problem...
11-15-2005, 07:17 AM   #4
BSOD

Join Date: May 2005
Posts: 2,734
Re: 1 = 2

Quote:
 Originally Posted by lhuser 2b=b - - 2 2 B=1
You're going to have to explain that.... not sure what you're trying to say.
Quote:
 Originally Posted by AOD god it 2 late :S i'm saying that 2= Cat X Mushroom all divided by a pony
Close.

 11-15-2005, 07:27 AM #5 In Runtime     Join Date: May 2004 Posts: 399 Re: 1 = 2 (A + B)(A - B) = B(A - B) Here's where you start to go wrong. The equation above equates to: A^2 - AB + BA - B^2 = BA - B^2 => BA - B^2 = 0 => BA = B^2 => B x A = B x B => A = B where ^ is "to the power of". I think you have to multiply out the brackets before simplifying your answer. OR if you don't assume that A=B, the same equation equates to: =>A^2 - AB = 0 =>A^2 = AB =>A x A = A x B =>A = B
11-15-2005, 08:21 AM   #6
Daemon Poster

Join Date: Mar 2005
Posts: 1,365
Re: 1 = 2

Quote:
 Originally Posted by lhuser 2b=b - - 2 2 B=1
Thats quite clear, you can't just divide b out of each side, you can only divide the number, thus it's completly screwed. Plus I dought A^2 = AB is hardly proven. Because if A was squared it would = a number, lets say:
A=2 B/=A (cannot equal) because if it was equal, it would also be considered A^2, so each side cannot equal each other from the start.
(starts to think...) unless:
A^2 = AB

(A^2)/A = (AB)/A
A=B :P
Meh it's certainly a f**ked up equation.

Chris
__________________
My Computer:
Mother Board: MSI K8N Neo4 Platinum/SLI --- CPU: AMD Athlon 64 3200+
PSU: OCZ ModStream 520w ----------------- HD: Seagate Barracuda 200g
Video Card: XFX GeForce 6200 -------------- RAM: OCZ Value ram Dual Channel 256 x2

11-15-2005, 12:36 PM   #7
BSOD

Join Date: May 2005
Posts: 2,734
Re: 1 = 2

Quote:
 Originally Posted by CJ The equation above equates to: (1)A^2 - AB + BA - B^2 = BA - B^2 (2)=> BA - B^2 = 0 (3)=> BA = B^2 (4)=> B x A = B x B (5)=> A = B where ^ is "to the power of". I think you have to multiply out the brackets before simplifying your answer. OR if you don't assume that A=B, the same equation equates to: =>A^2 - AB = 0 =>A^2 = AB =>A x A = A x B =>A = B
Step 1 is correct making it equal to the line before it:

AČ - BČ = AB - BČ

So to separate it into "(A + B)(A - B) = B(A - B)" is valid.

Your following steps (2-5) are also valid, but they don't make the proof untrue. It still works, as you can see, but you're getting warm.

11-15-2005, 12:45 PM   #8
BSOD

Join Date: May 2005
Posts: 2,734
Re: 1 = 2

Quote:
 Originally Posted by draconum Thats quite clear, you can't just divide b out of each side, you can only divide the number, thus it's completly screwed. Plus I dought A^2 = AB is hardly proven. Because if A was squared it would = a number, lets say: A=2 B/=A (cannot equal) because if it was equal, it would also be considered A^2, so each side cannot equal each other from the start. (starts to think...) unless: A^2 = AB (A^2)/A = (AB)/A A=B :P Meh it's certainly a f**ked up equation. Chris
I think you're confusing your algebra a bit. It's perfectly legal to divide B from both sides of the equation:

2B = B
2 = 1

The B variable cancels from both sides. Think about it as if B were a number. In fact, B is a number, we just don't know which one.

Also, AČ is equal to AB since we already know that A is equal to B.

Original equality:
AČ = AB
Expanded equality:
AA = AB
Cancel the A's:
A = B

This returns our already stated assumption therefore validating the procedure. Also, when you say that AB would be considered to be AČ, that's exactly what I'm saying when I set AČ equal to AB. You sort of proved that step to yourself in your question.

 11-15-2005, 03:26 PM #9 Fully Optimized     Join Date: Jan 2005 Posts: 2,468 Re: 1 = 2 How complicated can this thread get! __________________ 4GB Intel Core Duo - 1.25 GB DDR2 SDRAM
 11-15-2005, 05:53 PM #10 BSOD   Join Date: May 2005 Posts: 2,734 Re: 1 = 2 __________________